Effects of an oral health program on the occurrence of oral candidosis in a long-term care facility - Budtz-Jørgensen E, Mojon E, Rentsch A, Deslauriers N (Blackwell Synergy, 2000)
The aim was to evaluate the effectiveness of a preventive oral health program on the prevalence of oral candidosis in 237 frail or dependent residents in a long-term care facility. Half of the residents were included in an experimental group which benefited from a preventive oral hygiene program including instruction of the carers and implementation of a recall program for professional oral hygiene care. Methods: Intraoral examinations and yeast cultures from the oral mucosa and the fitting denture surface were carried out at baseline and 18 months later. The outgrowth of yeast was estimated on Oricult-N dip slides using the scale: no growth; 1–20 colonies; 21–100 colonies; ±100 colonies. Results: At baseline (n½237) and at 18 months (n½159) the experimental and the control groups were similar with regard to the residents’ distribution by age, sex, dental and prosthetic status and prevalence of denture stomatitis.